(untitled) (Research, Society and Development, 2020)
The Federal University of Campina Grande (UFCG), headquarters campus, has a lagoon in its perimeter, popularly known as “Laguinho”, which receives sanitary effluent from the internal area and from neighboring neighborhoods, and is currently used for irrigation of green areas of the campus . In view of this panorama, the present study was conceived and, consequently, had its general objective outlined as follows: Conduct an Environmental Impact Assessment (EIA) of a general and introductory character in the pond of UFCG in order to raise its current state, pointing out measures mitigating and compensating for negative impacts and valuing positive impacts, thus contributing to UFCG’s environmental management. The methodology of the present study involved bibliographic survey, on-site visits carried out from May 1st to 23rd, 2019 and informal conversation with IES employees and teachers. Data analysis was done through the triangulation between secondary data analysis, primary data and researchers’ inferences through direct on-site observation. It is noteworthy that a specific and robust methodology and techniques pertaining to an EIA were not adopted, but an assessment of an introductory and general character supported by the existing scientific productions on the subject on screen and in the Checklist method. Therefore, UFCG’s pond is an important space in the academic environment and in the urban area. Its construction was made possible to solve problems related to pollution, drainage, sanitation, landscaping, water scarcity and increase in the quality of life of the academic community. However, it is inappropriate for these conditions.